2011
DOI: 10.1021/jm1013924
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Permeable and Plasma-Stable Peptidomimetic Inhibitors of the Postsynaptic Density-95/N-Methyl-d-Aspartate Receptor Interaction

Abstract: The protein--protein interaction between the NMDA receptor and its intracellular scaffolding protein, PSD-95, is a potential target for treating ischemic brain diseases, neuropathic pain, and Alzheimer's disease. We have previously demonstrated that N-alkylated tetrapeptides are potent inhibitors of this interaction, and here, this template is exploited for the development of blood plasma-stable and cell-permeable inhibitors. Initially, we explored both the amino acid sequence of the tetrapeptide and the natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
67
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 52 publications
2
67
0
Order By: Relevance
“…2A). Tat-N-dimer is thereby by far the most potent PDZ domain inhibitor described (15,(24)(25)(26), and provides a 1,000-fold increase in affinity relative to monomeric Tat-NR2B9c (K i ; mean AE SEM: 4;600 AE 300 nM, Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2A). Tat-N-dimer is thereby by far the most potent PDZ domain inhibitor described (15,(24)(25)(26), and provides a 1,000-fold increase in affinity relative to monomeric Tat-NR2B9c (K i ; mean AE SEM: 4;600 AE 300 nM, Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
“…The shallow and elongated binding pocket of PDZ domains generally favor binding of peptides or peptide analogues and so far no drug-like small-molecule inhibitors of PDZ domains with affinities below 5 μM have been identified (15). Accordingly, the most advanced PSD-95 inhibitor is a 20-mer peptide, Tat-NR2B9c (7,8,16), composed of nine amino acids corresponding to the C-terminal of the GluN2B subunit of the NMDA receptor, fused to the HIV-1 Tat peptide (17).…”
mentioning
confidence: 99%
“…This principle has been demonstrated for the interaction between the N-methyl-D-aspartate-type glutamate receptors and the scaffolding postsynaptic density protein 95 (PSD-95), which has been targeted by peptide-based inhibitors [47][48][49][50][51][52] . This approach has shown great promise both as a pharmacological tool 51,53 and, in particular, in the development of therapeutically relevant compounds 54,55 .…”
Section: When Interacting Withmentioning
confidence: 99%
“…12 However, in our hands it was found that even after further multiple additions of molar equivalents of Lawesson's reagent, incomplete reaction was observed with significant quantities of the starting dipeptide still present in each case. It was also found when using this method, that purification of the required thioamide peptide was laborious due to difficulties in separating the required compounds from by-products formed from the Lawesson's reagent.…”
mentioning
confidence: 58%